Forensic engineering 2022. selected papers from the Ninth Congress on Forensic Engineering, November 4-7, 2022 Denver, Colorado - Liu, Rui (Structural engineer); Mulea, Carmen C.; Parfit, M. Kevin; Cavalline, Tara (American Society of Civil Engineers, 2022)
Selected papers from the Ninth Congress on Forensic Engineering, held in Denver, Colorado, November 4-7, 2022. This collection contains 122 peer-reviewed papers on a wide variety of forensic engineering subjects. Topics include: building enclosures, including roofs, façades, and foundations; infrastructure performance; natural disasters and extreme conditions; technologies for forensic investigations; forensic engineering education; construction performance and safety; analysis, design, repairs, and remediation; material performance; and professional practice in forensic engineering.